IMPROVING COGNITIVE LEARNING OUTCOMES BY USING E-MODULES - Dyah Aniza Kismiati (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2020)
Abstract:This study aims to determine the effect of the use of e-modules in improving student cognitive learning outcomes. This type of research is a Research and Development study with ADDIE model with a nonequivalent pretest-posttest control group design. This product was validated by experts and was also limited to 21 class XI students. The research sample is 2 classes based on purposivesampling technique, class X MIPA 5 as a control class and class X MIPA 1 as an experimental class. The instrument used: a matter of cognitive learning outcomes. Data were analyzed through Independent Sample T-Test and Normalized Gain Score (N-Gain Score). The results showed that the developed E-module had a significant effect on students' cognitive learning outcomes as evidenced by the significance value of 0,000 <α 0.05 and the category of height increase from the N-Gain Score calculation of 0.846.Abstrak:Penelitian ini bertujuan untuk mengetahui pengaruh penggunaan e-modul dalam meningkatkan hasil belajar kognitif siswa. Jenis penelitian ini merupakan penelitian Research and Development dengan model ADDIE dengan desain nonequivalent pretest-posttest control group. Produk ini divalidasi oleh para ahli dan juga diujicobakan secara terbatas pada 21 siswa kelas XI. Sampel penelitian yaitu 2 kelas berdasarkan teknik purposive sampling, kelas X MIPA 5  sebagai kelas kontrol dan kelas X MIPA 1 sebagai kelas eksperimen. Instrumen yang digunakan adalah soal hasil belajar kognitif. Data dianalisis melalui Independent Sample T-Test dan Normalized Gain Score (N-Gain Score). Hasil  penelitian menunjukkan bahwa E-modul yang dikembangkan berpengaruh secara signifikan terhadap hasil belajar kognitif siswa yang dibuktikan dengan nilai signifikansi 0.000 <α 0.05 dan kategori peningkatan tinggi dari hasil penghitungan N-Gain Score sebesar 0.846.